치과위생사 역량에 따른 교육과정 현황 분석: G 대학 치위생학과 교육과정을 중심으로 - 배수명; Soo Myoung Bae; 신선정; Sun Jung Shin; 장종화; Jong Hwa Jang; 정원균; Won Gyun Chung; 신보미; Bo Mi Shin (Han'guk Ch'iwisaeng Hakhoe chi, 2016)
Objectives: The purpose of the study is to investigate and analyzed the current status of a dental hygiene curriculum according to the dental hygienist competency. Methods: The study subjects were 59 courses in the department of dental hygiene in G University from April 1 to May 30, 2015. Except for liberal arts, 51 courses were finally selected and analyzed for the relationship between the curriculum and competency. For each course, systematic reviews were made by subject name, core competency, achievement goals, lecture hours, weekly themes, and learning goals. Three experts in the dental hygiene evaluated and analyzed the association of competency and goals. Results: Each course was operated by the goal from one to twenty two competencies of dental hygiene. Achieving one item of competency in a course required 13 hours on the average from minimum 2 hours to maximum 30 hours. More than 20 courses were operated and more than 900 hours were necessary for achieving the competency. The competency included the contents of ‘Be able to utilize basic medical and dental knowledge in dental hygiene care and patient care’ among the dental hygiene competencies. Conclusions: Competency based dental hygiene education will provide theoretical background for defining the identity of dental hygienist as a health care worker and to encourage professionals who contribute to the recognition of healthy society. Further research should be continued for improving the competency.based dental hygiene curriculum and education methods for implementing the curriculum within the paradigm of health care services.